A short and validated multiple sclerosis‐specific health‐related quality of life measurement for routine medical practice. Issue 6 (20th February 2013) - Devy, R.; Lehert, P.; Varlan, E.; Genty, M.; Edan, G.
<x xml:space="preserve">Abstract</x> Background and purpose Patient‐reported health‐related quality of life (Hr‐QoL) is an essential end‐point to assess the efficacy of multiple sclerosis (MS) treatment. Most QoL tools were developed for clinical research, for which measurement accuracy is required, irrespective of ease of use or the human resources needed. In routine medical practice (RMP), time and resources are limited, requiring simple and quick tools. Our objective was to set up a Hr‐QoL measurement adapted for patients with MS, and providing an accurate estimate of Hr‐QoL, whilst remaining easy to use and interpret in the RMP context. Methods Literature searches, expert meetings and semi‐structured interviews were used to gather relevant items and dimensions of existing scales. Scale development included item reduction and dimension identification through a cross‐sectional observational study. The scale was validated on another independent representative sample. Statistically significant dimensions were identified using psychometric procedures, a Rasch polytomous model and iterative confirmatory factor analysis (CFA). Results From 12 potential dimensions, based on a sample of 331 patients with MS, the backward CFA identified physical, mental and energy dimensions, and item optimization selected 10 items constituting our Hr‐QoL scale prototype. Its validity was assessed in an independent study of 457 patients with MS, which provided statistical evidence of reliability, reproducibility in time, invariance with regard to population subgroups and overall fitting with a Rasch polytomous model. Conclusions Compared with existing alternatives, our 10‐item three‐dimensional Hr‐QoL measurement tool is adapted to RMP, and constitutes an adequate compromise between precision and ease of use in patients with MS.